2015
DOI: 10.1007/s12053-015-9340-8
|View full text |Cite
|
Sign up to set email alerts
|

A segmentation analysis: the case of photovoltaic in the Netherlands

Abstract: The paper presents the results of a survey analysis into the adoption and non-adoption of solar PV in Dutch households. It is based on a survey under 817 households undertaken in 2012. Households are aggregated into 4 groups based on whether the adoption is voluntary or involuntary (when people buy a house with solar panels) and whether or not the household can be considered a potential adopter or rejecter. For these four groups, we study and compare the characteristics of adopters and nonadopters of solar PV.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 12 publications
3
35
0
Order By: Relevance
“…Segments are constructed by using models which measures how different groups can be taken into and what metric should define those groups. [29] Vasseur & Kemp classified PV consumer in the Netherlands into four groups which were PV users (voluntary and involuntary) and non-users (potential users and rejecters) by examining segmentations such as demographic, geographic, psychologic, and behavior [30]. Those segmentations help to build a glimpse of which types of people use or reject a system.…”
Section: Market Segmentations Of Solar Pv Usersmentioning
confidence: 99%
See 1 more Smart Citation
“…Segments are constructed by using models which measures how different groups can be taken into and what metric should define those groups. [29] Vasseur & Kemp classified PV consumer in the Netherlands into four groups which were PV users (voluntary and involuntary) and non-users (potential users and rejecters) by examining segmentations such as demographic, geographic, psychologic, and behavior [30]. Those segmentations help to build a glimpse of which types of people use or reject a system.…”
Section: Market Segmentations Of Solar Pv Usersmentioning
confidence: 99%
“…A decreasing trend of average total installation cost includes the decrease of sub-installation parts [29]. The installation cost consists of PV module price and a balance of system price.…”
Section: Scenariosmentioning
confidence: 99%
“…In 2018, photovoltaics 1 accounted for only a small share of 4.5% of the total net electricity generation in the European Union (EU, Jäger-Waldau 2018), whereas rooftop photovoltaics alone have the potential to grow to a quarter of total electricity demand (Bódis et al 2019). To facilitate this uptake, previous studies have demonstrated that tailoring messages to targeted homeowners is more effective than a 'one-size-fits-all' approach (Wolske et al 2018;Vasseur and Kemp 2015b;Sachs et al 2019). However, more insight into potential RPV adopters is needed to make policy actions, communication and marketing campaigns more effective by targeting specific groups (Petrovich et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies demonstrate that a high level of environmental concern will enhance RPV adoption (J. Palm and Eriksson 2018;Petrovich et al 2019;Vasseur and Kemp 2015b), whereas a quantitative study by Wolske et al (2017, n = 904), among potential adopters in the USA, demonstrates that pro-environmental norms only indirectly increase the interest in RPV through perceived personal benefits. Moreover, a study by Schelly (2014, n = 48), based on qualitative interviews with RPV adopters in Wisconsin (USA), points out that environmental values alone are not sufficient and/or not always needed for RPV adoption.…”
Section: Introductionmentioning
confidence: 99%
“…A brief review of recent European studies focused on this line of research is summarized in Table 2. [38] The Netherlands Electricity cost-savings and costs of PV system Self-sufficiency and contribution to a better natural environment…”
Section: Introductionmentioning
confidence: 99%